Javanese Islam: The Flow of Creed - Jamhari Jamhari (Studia Islamika, 2002)
In this article, popular Islam meaning Islam that is practiced and interpreted in accordance with local context is considered to be "the true Islam". To reach this ultimate religious goal, one may proceed through various ways of understanding Islam. These differences may indicate the level of religious understanding one has reached. On the other hand, they may demonstrate the many ways to grasp the truth of religious understanding. The emergence of various religious orientations with their different ways of understanding Islam indicates the ongoing process connecting Islam in Java with the wider context of Islam as a whole. This means that the different interpretations in Java are part of the global debate in Islam.DOI: 10.15408/sdi.v9i2.665